Analisis Estimasi Biaya Pemeliharaan Jalan Kabupaten di Kabupaten Cirebon - Hakiim, Chevy Helmi; Mudiyono, Rachmat; Adi, Henny Pratiwi (VISA: Journal of Vision and Ideas, 2025)
The condition of district roads in Cirebon, which continues to deteriorate each year, has encouraged the Cirebon District Government to continuously strive to carry out road maintenance. However, limited funding has become an obstacle to meeting all maintenance needs. Therefore, this study is considered important to assist the Cirebon District Government in managing district roads, particularly in road maintenance activities, to ensure that both maintenance methods and costs are implemented effectively and efficiently. This study uses the Surface Distress Index (SDI) method. Data collection was carried out through direct surveys of road damage as primary data. Several factors were identified in assessing pavement damage, including surface condition, type and width of cracks, percentage of cracking, number and size of potholes, wheel path depressions, edge damage, and the condition of other road ancillary structures. The results of the study conclude that out of the total length of the Sindanglaut–Pabuaran road, which is 14.1 km, 8.1 km is in good condition and requires routine maintenance, 2.8 km is in fair condition and requires periodic maintenance, 1.3 km is in lightly damaged condition and requires rehabilitation, and 1.9 km is in severely damaged condition and requires reconstruction. A maintenance budget of IDR 14,830,250,000.00 is required to restore and maintain the road in good condition.